Qualidade fisiológica e desempenho agronômico de sementes de soja em função do vigor e danos presentes - Zanachi, Letícia Delavalentina (2023)
When planting soybeans, one of the main attributes of the physiologic quality of soybean seeds to be considered is vigor. Therefore, the purpose of this paper was to evaluate the physiologic characteristics of the seeds and the agronomic performance of a soybean cultivar regarding vigor and damage present in the seeds. Seeds of the cultivar M 6410 IPRO were used, with three levels of vigor (high, medium and low) and with two different types of damage (moisture deterioration and mechanical damage). The experiment took place in the laboratory and in the field, using a completely randomized design for the former and a randomized block design for the latter; both with four replications. The seeds used were evaluated through the following tests: germination, accelerated aging, tetrazolium, electrical conductivity, seedling emergence in the field and emergence speed index. Field performance was evaluated through the production components: plant height, number of pods per plant, number of seeds per pod, initial and final number of plants per area and productivity (kg.ha-1). The results obtained were subjected to analysis of variance and, when significant, evaluated using the Tukey test. Results showed that damages, mainly those caused by deterioration due to humidity, interfered with the decrease in vigor and seed development in the field. And that the use of high quality seeds, that is, with less than 4% damage levels present, provided increases of around 25% in the productivity of the soybean crop.